Science and ski jumping - what next? - Kojonkoski, M. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Research in ski jumping in Finland has started in the turn of 1970's and since then the University of Jyväskylä has played an important role in this area. Many studies have been published related to biomechanics in ski jumping by Paavo Komi and Mikko Virmavirta as the main researches. Ground reaction forces, pressure distribution, muscle activation have been measured and combined with motion analysis in laboratory, wind tunnel and in field conditions. International co-operation has taken place in several winter Olympics over the past decades.